ANALISIS KARAKTERISTIK DAN KEBUTUHAN PARKIR TERMINAL KARGO DI KOTA DENPASAR - Arishandi, Nyoman Gery; Suthanaya, P. Alit; Wedagama, D.M. Priyantha (JURNAL SPEKTRAN, 2017)
Abstract: Cargo Terminal which has 70 units space is holding control of freight passing through the city center and as a place of loading and unloading of goods vehicles which do not have a warehouse. However, the activity of loading and unloading of goods is still widely practiced in the right of way which causes traffic jams. This triggers the Denpasar government to develop Terminal Kargo Denpasar  so as to supply the demand for parking and loading and unloading activities. The purpose of this study was to analyze the characteristics of the parking and future parking needs in developing Terminal Kargo Denpasar  . The method used to obtain data through direct surveys such as  inventory survey and survey cordon parking and secondary data obtained from the relevant agencies. The analysis shows the volume of parking of vehicles is 44,5 vehicles / hour, parking capacity is 36 vehicles / hour, parking supply as much as 372 vehicles and 4 for Parking Index that indicates there has been a problem of parking in the Terminal Cargo Denpasar. It is show Terminal Kargo Denpasar  has been unable to supply activity goods vehicles. The amount of the parking requirements for development of Terminal Kargo based on parking characteristic analysis are 101 spaces.
Keywords: Transport of goods, parking characteristics, parking needs.